GBA‐Related Parkinson's Disease: Dissection of Genotype–Phenotype Correlates in a Large Italian Cohort. Issue 11 (13th July 2020) - Petrucci, Simona; Ginevrino, Monia; Trezzi, Ilaria; Monfrini, Edoardo; Ricciardi, Lucia; Albanese, Alberto; Avenali, Micol; Barone, Paolo; Bentivoglio, Anna Rita; Bonifati, Vincenzo; Bove, Francesco; Bonanni, Laura; et al.
Abstract: Background: Variants in GBA are the most common genetic risk factor for Parkinson's disease (PD). The impact of different variants on the PD clinical spectrum is still unclear. Objectives: We determined the frequency of GBA ‐related PD in Italy and correlated GBA variants with motor and nonmotor features and their occurrence over time. Methods: Sanger sequencing of the whole GBA gene was performed. Variants were classified as mild, severe, complex, and risk. β‐glucocerebrosidase activity was measured. The Kaplan‐Meier method and Cox proportional hazard regression models were performed. Results: Among 874 patients with PD, 36 variants were detected in 14.3%, including 20.4% early onset. Patients with GBA‐PD had earlier and more frequent occurrence of several nonmotor symptoms. Patients with severe and complex GBA‐PD had the highest burden of symptoms and a higher risk of hallucinations and cognitive impairment. Complex GBA‐PD had the lowest β‐glucocerebrosidase activity. Conclusions: GBA‐PD is highly prevalent in Italy. Different types of mutations underlie distinct phenotypic profiles. © 2020 International Parkinson and Movement Disorder Society